Photobiomodulation Using Different Infrared Light Sources Promotes Muscle Precursor Cells Migration and Proliferation - Renan Lovisetto; Tainá Caroline dos Santos Malavazzi; Lucas Andreo; Maria Fernanda Setubal Destro Rodrigues; Sandra Kalil Bussadori; Kristianne Porta Santos Fernandes; Raquel Agnelli Mesquita-Ferrari (Photonics, 2022)
Photobiomodulation (PBM) has demonstrated positive effects on the muscle repair process. The aim of the study was to evaluate the effects of infrared PBM using different light sources—low-level laser (LLL) at 780 nm (40 or 70 mW, 10 J/cm2, 0.4 J) or LED at 850 nm (40 or 70 mW, 0.13 J/cm2, 0.4 J)—and dosimetric parameters on the proliferation and migration of muscle cells. The results showed that LLL 40 mW and 70 mW, with the same radiation exposure, led to an increase in proliferation after 24 h, but no differences at 48 and 72 h. Cells irradiated with LED 70 mW exhibited an increase in proliferation in comparison to the control group and 40mW after 24 and 48 h, but not at 72 h. Moreover, cell migration was greater in comparison to the control after 6 and 24 h, and no differences were found at 12 h when LLL was used with an output power of 70 mW. Furthermore, no differences were found at 6 and 12 h with the 70 mW output power-LED, but an increase was observed in the cell migration after 24 h. In conclusion, PBM using different light sources and dosimetric parameters was able to modulate the proliferation of C2C12 myoblasts, but only PBM at 70 mW was able to modulate the migration of these cells.